PENGARUH KEHAMILAN DAN PERSALINAN TERHADAP KESEHATAN MENTAL NARAPIDANA WANITA DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Saleh, Muhamad Azan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research investigates the impact of pregnancy and childbirth on the mental health of female prisoners in correctional facilities. The urgency of this study arises from the increasing number of incarcerated women who face unique psychological challenges during and after pregnancy. A qualitative methodology was employed, involving interviews with 30 female inmates who experienced pregnancy while incarcerated. The findings indicate a significant correlation between pregnancy-related stressors and deteriorating mental health, exacerbated by inadequate prenatal care and separation from newborns. This study underscores the necessity for improved mental health support and healthcare services for pregnant incarcerated women to mitigate adverse outcomes and promote well-being.Keywordspregnancy; childbirth; mental health; female prisoners; correctional facilities.